2000
DOI: 10.1074/jbc.m002203200
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Kinase C-dependent Phosphorylation of Serine 166 Is Controlled by the Phospholipid Species Bound to the Phosphatidylinositol Transfer Protein α

Abstract: The charge isomers of bovine brain PI-TP␣ (i.e. PI-TP␣I containing a phosphatidylinositol (PI) molecule and PI-TP␣II containing a phosphatidylcholine (PC) molecule) were phosphorylated in vitro by rat brain protein kinase C (PKC) at different rates. From the doublereciprocal plot, it was estimated that the V max values for PI-TP␣I and II were 2.0 and 6.0 nmol/min, respectively; the K m values for both charge isomers were about equal, i.e. 0.7 M. Phosphorylation of charge isomers of recombinant mouse PI-TP␣ con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 32 publications
3
46
0
Order By: Relevance
“…Phosphorylation of Nir2 at its PI-transfer domain by DAG-activated Golgi localized PKCs, could also provide a mechanism for negatively regulating DAG levels in the Golgi. Previous studies on PI-transfer proteins have shown that phosphorylation of highly conserved residues affects their PI/PC-exchange activity (van Tiel et al, 2000;Morgan et al, 2004). Thus, it could be that similar phosphorylation in the PI-transfer domain of Nir2 affects its PI-and/or-PCtransfer activity, thereby inhibiting DAG production and/or accelerating its consumption.…”
Section: Vap-dependent Lipid Transfer Regulates Golgi Functionmentioning
confidence: 98%
“…Phosphorylation of Nir2 at its PI-transfer domain by DAG-activated Golgi localized PKCs, could also provide a mechanism for negatively regulating DAG levels in the Golgi. Previous studies on PI-transfer proteins have shown that phosphorylation of highly conserved residues affects their PI/PC-exchange activity (van Tiel et al, 2000;Morgan et al, 2004). Thus, it could be that similar phosphorylation in the PI-transfer domain of Nir2 affects its PI-and/or-PCtransfer activity, thereby inhibiting DAG production and/or accelerating its consumption.…”
Section: Vap-dependent Lipid Transfer Regulates Golgi Functionmentioning
confidence: 98%
“…More specifically, Snoek et al (2004) have proposed that interaction of PI-TPa with the membrane may induce a slight reorientation of helix F. Since Ser166 is located at a distance of about 6 Å above the axis of helix F, this reorientation could trigger a slight conformational change leading to solvent exposure of the g-OH function of Ser166. Based on a kinetic analysis it was observed that the PCcontaining form of PI-TPa was phosphorylated at a faster rate than the PI-containing form (van Tiel et al, 2000). In line with this, the mutant PI-TPa(T59A), which is unable to bind PI, was a better substrate for PKC than the wtPI-TPa .…”
Section: Phosphorylation Of Solvent-inaccessible Ser166mentioning
confidence: 75%
“…PI-TPa and PI-TPb are substrates for protein kinase C (van Tiel et al, 2000(van Tiel et al, , 2002. Phosphoamino acid analysis of in vitro 32 P-labeled PI-TPs demonstrated that both isoforms were exclusively phosphorylated on a serine residue.…”
Section: Phosphorylation Of Solvent-inaccessible Ser166mentioning
confidence: 99%
See 2 more Smart Citations